1997
DOI: 10.1037/0033-2909.121.3.417
|View full text |Cite
|
Sign up to set email alerts
|

A stitch in time: Self-regulation and proactive coping.

Abstract: In a conceptual and temporal framework, derived from research on social cognition, social interaction, and stress and coping, the authors analyze the processes through which people anticipate or detect potential stressors and act in advance to prevent them or to mute their impact (proactive coping). The framework specifies five stages in proactive coping: (1) resource accumulation, (2) recognition of potential stressors, (3) initial appraisal, (4) preliminary coping efforts, and (5) elicitation and use of feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
1,304
2
30

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,281 publications
(1,385 citation statements)
references
References 207 publications
(219 reference statements)
49
1,304
2
30
Order By: Relevance
“…The stress-generating role of avoidance coping identifies a key path by which these coping strategies are linked to psychological distress. From a preventive perspective, this finding reinforces Aspinwall and Taylor's (1997) call for research on proactive coping. Active, future-directed coping efforts may operate as a positive analog of the present model, reducing future stressors and, indirectly, protecting against subsequent depressive reactions.…”
Section: Discussionsupporting
confidence: 69%
“…The stress-generating role of avoidance coping identifies a key path by which these coping strategies are linked to psychological distress. From a preventive perspective, this finding reinforces Aspinwall and Taylor's (1997) call for research on proactive coping. Active, future-directed coping efforts may operate as a positive analog of the present model, reducing future stressors and, indirectly, protecting against subsequent depressive reactions.…”
Section: Discussionsupporting
confidence: 69%
“…Important for building the case for confidence, such employee concerns over their work are typically linked to a perceived lack of confidence to handle work demands rather than to the objective difficulty of executing such demands (Lazarus & Folkman, 1984;Lazarus & Launier, 1978). I suggest that, in a rapidly changing workplace, employees may become less motivated or even demotivated (Armenakis & Bedeian, 1999;Aspinwall & Taylor, 1997) if they are not confident to handle changing work conditions. Work motivation theories have suggested that successful performance needs both skill and desire (e.g., Maier, 1955;Porter & Lawler, 1968).…”
Section: New Webster's Dictionary and Thesaurus Of The English Languamentioning
confidence: 99%
“…The use of substances as a way of coping is also included here (in contrast to substance use habits that develop earlier in life, which are included in the personal system). Coping efforts that are undertaken to prevent or anticipate problems prior to their occurrence are included as proactive coping and goal striving (Aspinwall & Taylor, 1997). As seen in Fig.…”
Section: A New Integrative Modelmentioning
confidence: 99%
“…), and substance use as a way of coping. Proactive coping and goal striving, which are used as preventive measures, are also included in this category (Aspinwall & Taylor, 1997). …”
Section: Coping and Functioning/well-beingmentioning
confidence: 99%